A closer look at grandiose narcissism: A revised version of the narcissistic personality inventory using a single-stimulus Likert format among Chinese adolescents and adults. (July 2022) - He, Ziyi Zoey; Yu, Shi
Abstract: Despite its extensive use and profound impact, the Narcissistic Personality Inventory (NPI; Raskin & Terry, 1988) has been continuously criticized on its forced-choice format, questionable contents and unstable structure. This research mainly aimed to (a) untangle main issues of the NPI and develop a revised version (NPI-r; NPI-rb as its brief variant), (b) offer insights into psychometric properties of the Likert-style NPI and the nuanced structure of grandiose narcissism, and (c) provide a closer look at grandiose narcissists by comparing their self- versus informant-report profiles. Bi-factor exploratory structural equation modelling and comparison of nomological networks of the NPI versions were performed with two Chinese samples ( N 1 = 317 adults, age M = 26.9, SD = 6.1, 48% male; N 2 = 269 adolescents, age M = 16.8, SD = 0.7, 49% male, with 142 informants). Results recommended the NPI-r and NPI-rb as better versions with improved psychometric properties and content validity. This research also underscored the unique roles of specific narcissistic traits, and found nomological networks of NPI versions in China consistent with previous evidence using Caucasian samples. Notably, the discrepancy between narcissists' self-report and informant-perceived profiles suggested some caution about the credibility of self-report data in narcissism studies. Highlights: The forced-choice NPI is outdated and not recommended for future studies. The 20-item revised NPI is provided to measure five core narcissistic traits. Underlying factor patterns and nomological networks differ across NPI-r subscales. Grandiose narcissists portray themselves as better than how others perceive them Grandiose narcissists tend to distort their personality and wellbeing in self-report.